Co‐deposition behavior of alumina nanoparticles and properties of Ni‐Al2O3 nanocomposite coatings. (29th April 2015) - Sadeghi, A.; Sieber, M.; Scharf, I.; Lampke, T.
<x xml:space="preserve">Abstract</x> The influence of adding alfa‐Al2O3 nanoparticles with different concentrations into Watt's bath under the application of ultrasound during electrodeposition was investigated by means of electrochemical impedance spectroscopy (EIS) in the galvanostatic mode. The characteristics of the double layer during nickel deposition were affected by the existence of Al2O3 nanoparticles in the electrolyte. In this study, the results of the impedance were correlated with the layer properties, e.g. the mean grain size, the incorporation of particles in the deposit and the strengthening performance. It became obvious that there is a good relationship between the EIS data and layer properties, which makes the impedance spectroscopy a reliable tool for predicting the properties in dispersion coatings. Copyright © 2015 John Wiley & Sons, Ltd.